Unhealthy Diets among Adult Populations in Sleman Districts, Yogyakarta: Pattern and Related Sociodemographic Determinants, Findings from Sleman HDSS - Septi Kurnia Lestari; Yayuk Hartriyanti; Ratri Kusuma Wardani (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2022)
Background: In Yogyakarta Province, the Sleman Regency has the second-highest life expectancy at birth and a high prevalence of non-communicable diseases (NCDs). One of the common NCD risk factors is an unhealthy diet. Thus, it is important to understand the factors that influence an unhealthy diet.Objective: This study aimed to determine sociodemographic factors associated with an unhealthy diet intake in the Sleman Regency population.Materials and Methods: Cross-sectional data from 4,963 adult respondents of the Sleman Health and Demographic Surveillance System was analyzed. A Descriptive test was done to measure the consumption frequency of sweet food and beverages, salty food, high-fat food, and food with monosodium glutamate (MSG). Generalized logistic regression was used to determine socioeconomic factors (residential area, age, gender, education level, marital status, and household wealth) that were associated with a higher frequency of unhealthy food consumption.Results: The majority of respondents reported frequent consumption of sweet food and beverages (82.4%), food that contains high fat (62%), and MSG (75.5%). About 46% of respondents reported frequent consumption of salty food.Conclusion: Education level, sex, age, household wealth status, and residential area are important determinants of a healthy diet.